Hetero-shaped coral-like catalysts through metal-support interaction between nitrogen-doped graphene quantum dots and PtPd alloy for oxygen reduction reaction. (20th December 2020) - Liu, Shanshan; Wang, Wei; Hu, Yanli; Tian, Feng; Miao, Xiaran; Liu, Liangsen; Xu, Zhiwei
Highlights: High catalytic catalysts are prepared by γ-rays and metal-support interaction. Ligand effect favors the decline of reaction energy barrier for ORR. Metal-support interaction is beneficial to increase the stability of ORR. Coral-like catalyst is prone to expose active sites coral-like morphology. Abstract: The development of efficient and durable electrocatalysts is essential for the practical application of fuel cells. Metal-support interaction (MSI) is an important concept in heterogeneous catalysis, which can construct the structure of catalyst and improve the reaction activity and stability of catalyst. Based on this, a simple and efficient method is innovatively proposed to synthesize coral-like special structure catalyst by utilizing the crush capacity of high energy γ-rays and the structure-induced effect of MSI between PtPd alloy and nitrogen-doped graphene quantum dots. The electrocatalyst demonstrates superior long-term durability due to the structure of catalyst is not easy to collapse under suitable MSI. Meanwhile, the unique coral-like structure provides a larger contact area, abundant mass transfer channels, and full exposure of active sites, which are advantageous to improve electrocatalytic activity. The oxygen reduction reaction performance of optimal catalyst (NGQDs140 -PtPd) was far superior to that of the commercial 20% Pt/C in alkaline medium, including onset potential (959 mV), half-wave potential (860 mV) and stability (the residual current density was 86.5% after long-term stability test). Therefore, coral-like shaped catalysts are expected to become a member of high-efficiency oxygen reduction catalysts in practical applications. Graphical abstract: Image, graphical abstract